The fly has an average velocity of
v[ave] = ∆x/∆t = (-5.80 m) / (4.22 s) ≈ -1.37 m/s
If its acceleration is constant, then its average velocity is also equal to the average of its initial and final velocities,
v[ave] = (v[initial] + v[final]) / 2
which tells us that
v[initial] ≈ -1.37 m/s - 1/2 v[final]
The fly's final velocity after some time t is given by
v[final] = v[initial] + (-1.33 m/s²) t
so that after 4.22 s, we have
v[final] ≈ v[initial] - 5.61 m/s
Substitute this into the equation for v[initial] :
v[initial] ≈ -1.37 m/s - 1/2 (v[initial] - 5.61 m/s)
Solve for v[initial] :
3/2 v[initial] ≈ -1.37 m/s + 1/2 (5.61 m/s)
⇒ v[initial] ≈ 0.955 m/s